Improvement and implementation of central sterile supply department training program based on action research - Ting Hu; Juanli Huang; Sixing Jiang; Ruixue Hu; Yongdeng Huang; Wei Pan; Liangying Yi (BMC, 2024)
Abstract Background This study aimed to improve and implement the central sterile supply department (CSSD) training program through action research and to evaluate its effect. Materials and methods The project was underpinned by action research. The problems that occurred in training were identified following scenario analysis, interviews, group discussions, and expert consultation to develop improvement measures. The training program characterized by CSSD was developed in the spiral circular process of "Plan-Act-Observe-Reflect". Results After the two rounds of training, the CSSD nurses significantly improved their professional knowledge, skills, and satisfaction with training compared with those before improvement. The nurses' overall satisfaction with the training and their performance improved. Conclusions The implementation of the training program designed based on action research can improve CSSD nurses' professional knowledge and skills and increase their enthusiasm for learning, laying the foundation for CSSD talent development.